Ischemic necrosis of all fingers and toes after norepinephrine use in gynecological patient - Pacheco Pacori, Yvan Denis (2018)
We present a female patient of 39 years old, who in october 2016 was treated at our institution (Dr. Negrin Hospital, Canary Islands-Spain), with necrosis of all fingers and toes, referred to the Plastic Surgery Service from the Intensive Care Medicine. It was a patient diagnosed with abdominal septic shock of pelvic origin due to vaginal ring infection. In the intensive care unit, the patient was treated with norepinephrine for 5 days. This catecholamine stimulates the adrenergic receptors, causing vasoconstriction and increased blood pressure. After ten days of treatment, the patient presents with ischemic necrosis of all fingers and toes, and amputation is necessary, with aesthetic and functional sequelae.